BDNF Contributes to the Genetic Variance of Milk Fat Yield in German Holstein Cattle - Zielke, Lea G.; Bortfeldt, Ralf H.; Tetens, Jens; Brockmann, Gudrun A. (Frontiers in Genetics, 2011)
Abstract The gene encoding the brain derived neurotrophic factor (BDNF) has been repeatedly associated with human obesity. As such, it could also contribute to the regulation of energy partitioning and the amount of secreted milk fat during lactation, which plays an important role in milk production in dairy cattle. Therefore, we performed an association study using estimated breeding values of bulls and yield deviations of German Holstein dairy cattle to test the effect of BDNF on milk fat yield. A highly significant effect (corrected p-value =3.362 x10-4) was identified for an SNP 168 kb up-stream of the BDNF transcription start. The association tests provided evidence for an additive allele effect of 5.13 kg of fat per lactation on the estimated breeding value for milk fat yield in bulls and 6.80 kg of fat of the own production performance in cows explaining 1.72% and 0.60% of the phenotypic variance in the analysed populations, respectively. The analyses of bulls and cows consistently showed three haplotype groups that differed significantly from each other, suggesting at least two different mutations in the BDNF-region affecting the milk fat yield. The fat yield increasing alleles also had low but significant positive effects on protein and total milk yield which suggests a general role of the BDNF-region in energy partitioning, rather than a specific regulation of fat synthesis. The results obtained in dairy cattle suggest similar effects of BDNF on milk composition in other species, including man.